The influence of teachers’ psychological capital on the quality of work life: exploring the mediating impact of emotions - Erden, Hale (Frontiers in Psychology, 2025)
IntroductionThe aim of this study is to investigate whether emotions play a mediating role in determining the effect of teachers’ psychological capital (PsyCap) on the quality of work life (QWL).MethodsThe current study presents an investigation on the mediating role of emotions and their effect on teachers’ PsyCap at their work life. The study used scales including Psychological Capital Scale (PsyCapS), Quality of Work Life Scale (QWLS) and Emotions Scale (ES). The scales were all applied to administrators and teachers in state schools in TRNC. The sample of the study consists of 369 teachers and school administrators. Data were analyzed using SPSS 27.0 for descriptive statistics and correlation analyses. In addition, structural equation modeling was performed with AMOS to examine the potential mediating effect of emotions on the relationship between PsyCap and QWL.ResultsAs a result, the mediating role of emotions in the relationship between teachers’ PsyCap and perceptions of QWL was fully supported. There was a significant correlation between teachers’ PsyCap, perceptions of QWL and emotions. PsyCap was found to have a significant and positive effect on both emotions and perceptions of QWL. In addition, PsyCap was found to have a significant positive relationship with QWL.DiscussionAmong TRNC teachers, PsyCap has a significant positive relationship with both emotions and perceptions of QWL. PsyCap can directly or indirectly increase the perception of QWL through the relationship with emotions. Therefore, teachers’ positive PsyCap can positively increase their emotions and perceptions of QWL.